Strategy Formulation Methods used During Corporate Transformation in Global Context: Navigating the Transition: Effective Strategy Formulation in a Changing Global Landscape (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The study was able to uncover a pattern in their approach by utilising the core components ofthe strategy cascade and its septs. Furthermore, provide a thorough grasp of these companies' longtermdesires. Finding empirical evidence to validate the discovered trend utilising examples from thecorporate world employing the world's top disruptive firms was useful. The world is swiftly shifting fromthe industrial to the intelligent era, with far-reaching implications for both individuals and organisations.Because of the rapid rise of digital technology, considerable changes have occurred in worldwidestrategies and operations. It has been stated that transformation is modern society's attempt to preventextinction in the face of digital disruption. While it is critical for leaders to develop new strategies,business models, and organisational projects that embrace change, the true issue is directing theirpeople through the transition from their present state to their intended future state.